Flavonoid Compounds from Arundina graminifolia - Li, Yinke; Yang, Liying; Shu, Lidang; Shen, Yanqiong; Hu, Qiufen; Xia, Zhangyuan (Asian Journal of Chemistry, 2013)
A new flavonoid compounds, gramflavonoid A (1), together with four flavonoid compounds (2-5), were isolated from the whole plant of Arundina gramnifolia. The structure of 1-5 was elucidated by spectroscopic methods including extensive 1D and 2D NMR techniques. The anti HIV-1 activity was evaluated for compounds 1-5. The results reveal that compound 1 showed moderate anti HIV-1 activity and other compounds also showed weak anti HIV-1 activity.